Multi-stakeholders’ perception in popularization and dissemination of Farmer-led Innovations in Northern India - Kar, Priyajoy (Indian Journal of Dairy Science, 2024)
Agro-ecosystems are subjected to a variety of biotic and abiotic challenges, particularly in developing nations. Farmers' innovations are more quickly adopted by other farmers since they are affordable, accessible, locally relevant, and proven in a real farm setting. The proposed study was conducted in Haryana and Punjab, as these two states hold the greatest number of innovative farmers in India in dairy sector as compiled from different secondary sources. Each state had two districts chosen at random. A sample size of 70 dairy farmers from each district and 20 Research and Development sector persons (public and private) were selected, thus constituting a sample size of 360 for the study. The final regression model explained 74.60% of the variation and was significant (P > 0.001). Stakeholders were giving prominent importance to the costs of the innovation followed by the proper documentation of the innovations by any sort of internal/external agencies. Our results show that farmer-led innovations generally have a positive effect on welfare, which is consistent with growing arguments that these innovations which have often received less attention than externally pushed technologies should be encouraged as a supplement to efforts to improve food security and eradicate rural poverty.